Investigating the endoplasmic reticulum unfolded protein response and its role in sleep - Chakrabarty, A (2023)
Proteostasis involves regulating the synthesis, folding and quality control of proteins in the cell, and is essential for all cells in our body, including neurons in our brain. Errors in protein folding are dealt with by quality control mechanisms in the cell. One such mechanism is the Unfolded Protein Response (UPR), which is elicited by the accumulation of unfolded proteins in the endoplasmic reticulum (ER) under conditions of ER stress. The UPR is an adaptive process involved in maintaining proteostasis under normal physiological conditions, however, sustained or severe activation of the UPR can lead to cell death and has been implicated in pathological conditions. One process that has been linked with ER stress is sleep deprivation, which has been reported to increase levels of UPR activation in the cerebral cortex. Sleep deprivation is also associated with an increase in cortical slow wave activity (SWA) during subsequent non-REM sleep, reflecting increased sleep intensity. However, the effect of sleep deprivation upon the UPR has not been thoroughly characterised across different regions or cell types within cortex. Moreover, the potential role of the UPR in modulating cortical activity is not well understood. In this thesis, I aimed to investigate the interactions between the UPR and sleep in mice by addressing three central objectives. Firstly, I investigate whether different regions and cell populations within cortex undergo different degrees of UPR activation as a function of their sleep-wake history. Tissue-wide molecular biological assays and cell-specific quantitative immunohistochemical analyses are used to measure UPR levels across different regions and cell types in mouse cerebral cortex after a period of sleep deprivation. Sleep deprivation elicited a small but consistent upregulation of the UPR in the frontal region of cortex. Specifically, neuronal cells were identified to contribute to the sleep deprivation effect. However, inhibitory neurons did not display a sleep deprivation-induced UPR, suggesting that the UPR is a heterogenous process within cortex. Secondly, I examine the effects of the UPR triggered by ER stress on local cortical activity patterns during wake and sleep. Continuous electrophysiological recordings are performed during sleep and wake in freely-moving mice following pharmacological induction of the UPR in a local region of cortex. While no differences were observed in global sleep, changes were observed in neural activity patterns, including a consistent localised decrease in SWA magnitude during sleep. However, the outcomes indicated that the pharmacological approach results in severe activation of the UPR, which may not accurately reflect the physiological UPR that occurs with sleep deprivation. Thirdly, I investigate whether it is possible to develop a novel fluorescent reporter of a cell’s global UPR, which is optimised for the quantification of low levels of UPR and has improved kinetics. The resulting reporter, named sensor of UPR activity (sUPRa), showed substantial changes in fluorescence in response to a variety of UPR-activating stimuli. sUPRa reflected the temporal dynamics of UPR initiation and dissipation after drug treatment. Finally, sUPRa was leveraged to reveal the sleep deprivation-induced UPR in a subset of mouse cortical neurons. These properties validate the reporter as a useful tool for monitoring the dynamics of physiological UPR in individual neurons across the sleep-wake cycle, with the potential to genetically target cell populations. Together, this thesis suggests that the UPR is a heterogeneous process in cortex and highlights the need for more refined tools to monitor and manipulate the physiological UPR. Providing the field with an improved fluorescent reporter of UPR activation represents one step towards better understanding the relationship between UPR activation and sleep.